Field quality and surface resistance studies of a superconducting REBa2Cu3O7−x—Cu hybrid coating for the FCC beam screen. (1st April 2023) - Telles, G T; Romanov, A; Calatroni, S; Granados, X; Puig, T; Gutierrez, J
Abstract: To ensure beam stability in the future circular collider study of the European Organization for Nuclear Research, RE(=Y, Gd, Eu)Ba2 Cu3 O 7 − x high-temperature superconductor was proposed as a low-surface impedance coating for its beam screen. Unfortunately, persistent currents in the superconductor will degrade the magnetic field homogeneity inside the beam chamber, endangering the stability of the beam trajectory. To counteract this effect, we have explored the possibility of using a highly conductive hybrid coating made of Cu and REBa2 Cu3 O 7 − x . This decreases the surface impedance when compared to that of pure copper, while maintaining high magnetic field quality inside the beam screen chamber. This work formulates guidelines for hybrid coating geometries to comply with the field quality criterion of a circular accelerator during operation with dipole magnets by means of finite elements numerical analysis. We produced hybrid coating samples with compliant geometries via photolithography. Scanning Hall microscopy and radio-frequency characterization have given the first experimental confirmation that these hybrid coatings offer high field quality and present a surface resistance lower than that of copper for the beam screen of the future circular hadron collider. The excellent agreement shown between experimental results and simulations validates that the numerical analysis performed throughout this work can be used as a prediction tool for future proposed geometries.